STUDY OF THE LEACHING BEHAVIOR OF ZINC SULFIDE CONCENTRATE BY USING IRON- AND SULFUR-OXIDIZING BACTERIUM AND BIOSURFACTANT-PRODUCING BACTERIUM - ZULFIYAH , TITIN
Zinc is the fourth highest level of metals needed in the world. Zinc itself is widely contained in sphalerite, thus it allows processing of zinc extraction trough microbes such as bacteria. This process is known as bioleaching. Bioleaching process of sphalerite has evolved by using thermophilic bacteria using a high concentration of dissolved FeSO4.7H2O as an oxidizing agent. However, thermophilic bacteria mainly inhabit areas of acid mine discharge. The present study employ mixotrophic bacteria capable of oxidizing iron and sulfur as well as producing biosurfactants, which were isolated from mining areas of Indonesia to investigate the leaching behavior of zinc at room ambient temperature in order to minimize operating cost. This research began by determining the best bacteria in bioleaching experiments and discover the best bacteria for zinc recovery from sphalerite, namely Alicyclobacillus ferrooxydans and Pseudoclavibacter sp.. The starting sphalerite concentrates were characterized using X-Ray Difraction (XRD), X-Ray Fluorosence (XRF), Scanning Electron Microscope (SEM), dan FourierTransform Infrared Spectroscopy (FT-IR). Experimental parameters undertaken included the type of bacteria, dissolved FeSO4.7H2O concentration, bacteria inoculum concentration, pulp density and the presence of pyrite and sulfur to study the behavior of sphalerite concentrate leaching. Sampling was taken periodically once in 24 hours to observe the solubility and residue of the best solubility through FT-IR, XRD and SEM-EDX analysis. Experimental results showed that the bacterium Alicyclobacillus ferrooxydans was able to leach zinc from sphalerite concentrate with highest extraction level of 44.87% at 1% (w/v) pulp density, 20% (v/v) bacterial inoculum and 15 g/l FeSO4. 7H2O. The increased pulp density (5% w/v) resulted in the zinc extraction level of 25.19% at 15% (v/v) bacterial inoculum and 15 g/l FeSO4.7H2O. The presence of sulfur and pyrite did not give a significant effect on increasing zinc solubility, which only achieved extraction level of 17.28%. The bioleaching experiments using complex ores as a control experiment yielded the zinc recovery level of 65.44% at 5% (w/v) pulp density, 15% (v/v) bacterial inoculum and 15 g/l FeSO4.7H2O.. The use of a biosurfactant-producing bacteria Pseudoclavibacter sp. resulted in an extremely high zinc solubility (92.68%) from sphalerite concentrates at 1% (w/v) pulp density and 20% (v/v) bacterial inoculum.